ANALYSIS OF ENTERPRISES’ EFFICIENCY AND MULTIPLIER INDICATORS IN THE FORMATION OF AN INVESTMENT PORTFOLIO - Khaydarov Khumoyun Begmurod o‘g‘li (Modern American Journals, 2026)
In forming an investment portfolio, examining the efficiency (ROA, ROE) and multiplier (P/B, P/S, P/E) indicators of each enterprise included in the portfolio is an integral part of fundamental analysis. In this article, using the example of five joint-stock companies two banks and three non-bank companies the efficiency and multiplier indicators are analyzed over a period of years. Based on this analysis, relevant conclusions are drawn, and an effective investment portfolio is formed using the obtained results.
Keywords: Investment portfolio, ROA, ROE, P/B, P/S, P/E indicators, net profit margin, Uzbekistan Republican Commodity Exchange (UZRTXB), Hamkorbank JSC, Uzbektelecom, Chilonzor Goods Trade Complex, Uzsanoatqurilishbank JSC.